System for Recognition of Facial Expressions Using Machine Learning - Silva, Tharcio Thalles; Andrade, Alexsandra; da Silva, Natalia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
Artificial intelligence (AI) is a field of Computer Science that aims to simulate specific actions of humans and animals with improved performance. Another definition is that it is is manmade intelligence used and demonstrated by machines and devices in contrast to biological intelligence. Despite this objective, this area is still far from achieving significant goals. There are still many myths and exaggerations that surround it, which causes it to appear to be at its best state of the art, however, amid so many rumors, there are works that are really taking great steps to achieve such a performance exhibition. The present work proposes an Artificial Intelligence named Hill, able to recognize macro facial expressions in humans, using computer vision and the detected expressions for various applications, thus allowing the AI to adapt to other purposes that it can help, such as improving a type of learning of another AI that interacts with human beings, making its learning more thorough and contextualized.